Peningkatan Pengetahuan Lansia tentang Low Back Pain melalui Penyuluhan Kesehatan di Desa Punie Kecamatan Darul Imarah Kabupaten Aceh Besar - Muliati; Musfirah; Putri Ramadhani; Fiza Novita; Dina Ofiana; Sebegi Seperange (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
Lower back pain, or low back pain (LBP), is one of the musculoskeletal disorders caused by poor ergonomics. LBP is defined as pain localized between the costal margins and the inferior gluteal fold that lasts for more than one day. Low back pain is one of the most common complaints among people of various ages and backgrounds. This condition can disrupt daily activities, reduce productivity, and affect a person's quality of life. This community service aims to increase public knowledge on how to prevent and manage low back pain. The first step of this activity is coordinating with the Darul Imarah Community Health Center to determine the location and time for carrying out the activity. The implementation of this counseling activity began with introductions, explaining the purpose and objectives, distributing leaflets to the participants, presenting the material, and demonstrating techniques for handling Low Back Pain. The final stage of this activity was a Q&A session between the participants and the presenter. This counseling activity went smoothly and well, and there was a noticeable enthusiasm from the community, showing great interest in following the counseling session to the end.